Objectification of the results of the agility-test through the use of AI methods - Huber, A.; Hummel, C.; Rieder, M.; Spitzenpfeil, P.; Waibel, K. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Since 2016, the agility test [1] has been used in performance diagnostic tests and in the return-to-sport process of the German alpine skiing, ski cross and ski freestyle team athletes. While the test has proven in practice to be very effective in the return-to-sport process, the assessment of both the two landings and the 15 jumps was subjective, with three categories each: good, average and bad. The subjective assessment is to be expanded, objectified and, ideally, replaced by an AI-supported, automated kinematic evaluation (Nemo, Simi Reality Motion Systems GmbH ©, Unterschleißheim, Germany).